Versatility of an Extended Posterior Approach for the Treatment of Acetabular Fractures With Reference to the Superior Gluteal Neurovascular Bundle. Issue 8 (August 2016) - Studer, Patrick; Kosuge, Dennis; Rickman, Mark; Solomon, Lucian B.
Abstract : Summary: The superior gluteal neurovascular bundle is at risk of injury in certain types of acetabular fractures and the associated surgery. This article describes the versatility of an extended posterior approach, previously described for complex revision total hip replacement (the Adelaide approach) and for the treatment of acetabular fractures that allows a wide exposure of the ilium through identification, protection, and mobilization of the superior gluteal neurovascular bundle. Abstract : Supplemental Digital Content is Available in the Text.